Growth and yield performance of four generations of high amylose transgenic Adira 4 cassava - Enny Sudarmonowati; Hani Fitriani (Jurnal Ilmu Pertanian, 2021)
Attempt to improve cassava starch quality have been conducted by producing the first high amylose transgenic Adira 4 Indonesian cassava. This study aimed to evaluate agronomic performances of transgenic plants, assessment of four generations in specific containment screenhouse and limited field trial were conducted with improved method. The survival and growth rate of cuttings was enhanced by applying growth regulator such as Atonik and improving planting procedures. The growth and yield performances were measured by comparing related variables across four generations of selected lines. Dipping in 1 mL.L-1 Atonik solution with shading in the early planting were only required when the plant growth was poor and not favorable soil and weather. The result showed that survival of third and fourth generations of Lines A55-5 and A55-15 could reach 100 % when it was treated with Atonik. According to 14 lines assessed, Line A55-5 was one of the promising ones due to its growth, multiplication performance, and almost double amylose content compared to wild type. Meanwhile, Line A55-12 showed the highest yield. The finding will benefit functional food industries when appropriate gene construct and approaches were applied for better growth and yield results.